Migration and social preferences - Diego Mari\~no Fages; Matias Morales (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
Anti-immigrant sentiment is frequently motivated by the idea that migrants are a threat to the host country's culture (Rapoport et al., 2020). We contribute to the discussion by investigating whether migrants adapt their social preferences (SPs) to those prevalent in their host country. For this, we rely on a global and experimentally validated survey to show that migrants' preferences strongly correlate with their host population's SPs and provide some evidence of a causal relationship.
Keywords: F22; D01; 330; Migration; Assimilation; Social Preferences